A case report of cold autoimmune haemolyticanaemia in pulmonary tuberculosis - Zulkeflee, Razan Hayati; Nizam Akbar, Nurul Asyikin; Yusoff, Shafini; Hussin, Faezahtul Arbaeyah; Husin, Azlan; Zulkafli, Zefarina; Hassan, Mohd Nazri; Ramli, Marini; Abdullah, Marne; Iberahim, Salfarina; et al. (Bangladesh Journal of Medical Science, 2022)
Autoimmune hemolyticanemia (AIHA) can be caused by a variety of etiologies. Approximately one-half of warm AIHAs are idiopathic, while the nonidiopathicetiologies include lymphoproliferative disorders, autoimmune disease, and infection-induced AIHA. AIHA may be frequently challenged by infectious complications, mainly as a result of immunosuppressive treatments administered. Here we reported an extraordinary case of Mycobacterium tuberculosis infection presented with high titer cold-agglutinin autoimmune hemolysis in an immunocompetent patient. Although being risk factors for mortality, infections are an underestimated issue in AIHA. No antecedent case of pulmonary tuberculosis associated with cold agglutinin disease has been reported from Malaysia. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 754-757